ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN ON ASSETS PADA BANK UMUM SYARIAH DAN UNIT USAHA SYARIAH (PERIODE 2010-2013) - Budi Sukardi, Usnan Ade Setiawan (Jurnal Riset Keuangan dan Akuntansi, 2016)
This research based to analyze the impact of financing to deposit ratio (FDR), non perfoming finance (NPF), banking operational cost (BOPO), third party pooling fund (DPK), interest rate of central bank (BI Rate), and Inflation on return of Asset (ROA) determination Sharia Bank, this research had populate from Sharia Bank and Sharia Operational Unit during 4 years research (2010 - 2013).This research use a second type data which is known from monthly statisticÃ‚Â  Islamic Bank report published by Central Bank. The data was analyzed by double linier regretion with examine classic assumption before. The research result with parsial type (t-examine) proved that FDR, NPF, BI Rate and inflation are not impacted with ROA Islamic Bank determination and BOPO had an impact and third party pooling fund (DPK) exclude because that had a multikorealis disease so as stimultaneously analyze (F examine) NPF,FDR,BOPO, central bank interest, and infalation are significant impact to return of asset determination of Islamic Bank.